The Influence of Technical and Contextual Variables of the Last Stroke on Point Outcome in Men’s and Women’s Singles Badminton - Sheng, Yi; Yi, Qing; Gómez-Ruano, Miguel-Ángel; Chen, Peijie (Frontiers in Psychology, 2022)
The purpose of this study was to identify the effects of the technical and context-related variables of last strokes in rallies on the point outcomes of both men’s and women’s players in elite singles badminton matches. A total of 100 matches during the 2018 and 2019 seasons were analyzed, and the data of 4,080 men’s rallies and 4,339 women’s rallies were collected. The technical variables including strokes per rally, forehand strokes, overhead strokes, and defensive action, and the context-related variables including game status, result against serve, importance of rally, and importance of set, were modeled with Probit regression modeling as the predictor variables. The binary variables of “winner or not” and “error or not” were considered the response variables. The results showed that defensive actions had the greatest impacts on the winners and errors of both the men’s and women’s singles players, and the forehand and overhead strokes were negatively associated with the winners and errors of the women’s singles players and the winners of the men’s singles players. No significant effects were found for the strokes per rally on the winners and errors of the men’s singles players, while significant effects were found for the women’s singles players. The context-related variables appeared to have positive effects on the winners and negative effects on the errors of both sexes. These findings can provide important insights for coaches and players to evaluate their performances of last strokes in rallies and to improve training interventions and match tactics and strategies.